Deadpool/Wolverine. A time of Stryfe - Percy, Benjamin (Marvel Worldwide, Inc., 2026)
Wade and Logan -- together again! The most unlikely pairing turned the most demanded one, Deadpool and Wolverine must find a way to get along -- because the fate of the world hangs in the balance! When the deadly Stryfe resurfaces and his ages-long plan comes to fruition, you'll get to see a new side of our heroes -- because the only thing that stands between Earth and annihilation is the Best There Is and the Merc With the Mouth! Meanwhile, a third Weapon X alum joins the fun -- and Maverick wants answers! Featuring one of the Marvel Universe's oldest stars, Nick Fury Sr. -- and a brand-new one, the mutant Legacy! Your favorite super heroes get put through their paces in a series chock-full of surprises, twist reveals and a villainous plot that'll turn long-term and newly arriving X-readers' heads!COLLECTING: Deadpool/Wolverine (2025) #1-10